Conservative versus surgical therapy for idiopathic and secondary megacolon or megarectum in adults: a retrospective multicentre controlled study$dOriginalarbeit = Konservative versus chirurgische Therapie beim idiopathischen und sekundären Megakolon oder Megarektum im Erwachsenenalter : eine retrospektive multizentrische Kontrollstudie - Schmitz, Daniel; Meier, Emilia; Axt, Steffen; Arlt, Gerrit; Kienle, Peter; Johannink, Jonas; Königsrainer, Alfred; Mohammad, Owais; Jakobs, Ralf; Willis, Stefan; Demir, Ihsan Ekin; Friess, Helmut; et al. (Zeitschrift für Gastroenterologie, 2024)
Background Idiopathic and secondary megacolon (MC) and megarectum (MR) in adults is associated with persistent bowel dilatation and reduced intestinal motility. Little is known about the optimal treatment of this rare disease. Therefore, we retrospectively analysed long-term data from these patients in 5 community and university hospitals, focusing on conservative versus surgical treatment. Methods Patient records from 7/2004 to 9/2021 were screened for colorectal diseases with severe constipation and persistent megacolon ≥ 9.0 cm and/or megarectum ≥ 6.5 cm. Follow up-data was collected through telephone interviews and written surveys. ClinicalTrialsgov NCT04340856.Results Sixty-seven patients with idiopathic (n=10) and secondary (n=57) MC or MR were identified with only 20 of 67 patients (29.9%) correctly diagnosed. Mean/median age was 64/69 (range 18-93) years. Thirty-two patients were treated with laxative regimens, and 35 underwent surgery (colostomy: n=12, segmental resection, or hemicolectomy: n=10, (sub)total colectomy: n= 13) after conservative treatment attempts in 32/35 (91.4%). The mean/median follow-up was 4.2/2.7 (range 0.1-17.0) years. The readmission rate for MC-associated symptoms was significantly higher after conservative treatment than after surgical therapy at 12 (0.84 vs. 0.36 per patient, p=0.036), 24 (1.00 vs. 0.52, p=0.048) and 36 (1.13 vs. 0.58, p=0.047) months, as was the number of patients with persistent laxative dependence (28/32 (87.5%) vs. 19/33 (57.6%); p = 0.007). Therapy-associated adverse events (Clavien-Dindo classification) were documented more often in surgically treated patients (11/35, 31.4%) (p=0.025).Conclusion Surgical treatment may be considered earlier if idiopathic or secondary MC or MR is correctly diagnosed, and conservative treatment has been attempted.